Development of Interactive Multimedia Assisted with Articulate Storyline 3 Application Integrated with TPACK (Technological Pedagogical Content Knowledge) to Increase Student Learning Motivation - Aini, Zuhrotul; Haryanto, Haryanto; Miharti, Isra (ALACRITY : Journal of Education, 2025)
The employment of interactive learning media constitutes a pivotal component in enhancing learning efficacy within the digital era. Interactive media fosters learner engagement in educational activities, thereby addressing a prevalent challenge in chemistry education, namely the underutilisation of technology. The dearth of innovation and accessibility to learning materials contributes to students' diminished motivation in chemistry classes. The objective of this study was to develop interactive learning media, facilitated by the Articulate Storyline 3 application, employing the TPACK approach to support the teaching of naming chemical compounds in class XI IPA Man 2 Tebo.The research method employed a development (R&D) approach, following the Lee & Owens model, which comprises five stages: analysis, design, development, implementation, and evaluation.The findings indicate that the developed media is conducive to effective learning. This can be seen from the results of material validation with an average score of 84.6% which is in the value range of 81%-100% with the criteria “Very Feasible”, while the percentage of media expert validation scores of 67.6% is in the value range of 61%-80% with the category “Feasible” seen from the aspects of design, layout, and ease of use of the media. The results of using interactive learning media are proven to be able to increase student learning motivation, seen from the results of the student assessment questionnaire obtained a value of 94.35% which is on a value scale of 81%-100% with the value criteria “Very Good”. From the results of the study it can be concluded that the interactive learning media using Articulate Storyline developed is very feasible to be used as additional media in the learning process.